ACCURACY ANALYSIS ON THE EMPIRICAL EQUATION OF FINITE THICKNESS SEMI-ELLIPTICAL SURFACE CRACK BASED ON INTERACTION INTEGRAL METHOD - HOU Shuai; ZHU YouLi; QIU Ji; SUN XiaoFeng (Jixie qiangdu, 2018)
The interaction integral method（IIM） is used to calculate stress intensity factors（SIF） of finite thickness semi-elliptical surface cracks. Results are compared with that predicted by the empirical equation and equivalent domain integral（EDI） method. The comparison with EDI method verifies computational accuracy of IIM for calculating 3 D crack problem. The SIF distribution along the semi-elliptical crack of different crack shape ratio and different finite thickness ratio conditions are calculated with the IIM and empirical equation. Relative error of empirical equation is evaluated. The results show that empirical equation produces larger error when the finite thickness ratio is large. Based on the analysis, the applicable range of the empirical equation is presented.